Формування Конституційного Суду України як одна з умов забезпечення його легітимного функціонування - Ковальчук, В.; Kovalchuk, V.; Шабелько, Н.; Shabel’ko, N. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті наведено основні причини втрати народної легітимності Конституційним Судом України, запропоновано способи формування та критерії відбору на посаду судді Конституційного Суду України. Визначено можливості втілення Україною кращого європейського досвіду функціонування даного інституту з урахуванням національних особливостей країни. У статті встановлено, що роль органу конституційної юстиції у суспільстві та правовій і політичній системі сучасної конституційної, демократичної держави є надзвичайно вагомою. Конституційний Суд як орган конституційного контролю посідає важливе місце у механізмі легітимації державної влади, оскільки він покликаний захищати закріплені Конституцією суверенні права народу від протиправних дій та рішень органів публічної влади, надаючи їм додаткової легітимності. The article presents the main reasons for the lossof popular legitimacy of the Constitutional Court of Ukraine and suggeststhe ways and methods of perfecting the Constitutional Court of Ukraine and elaboration of criteria for the post of judge in it. The author convincingly proves the possibility of applying in Ukraine the European experience of this institution functioning, taking into account national peculiarities of the country. This articlestates that the role of constitutional justice in society and especially for the legal- political system of modern constitutional democratic state is extremely significant. The Constitutional Court as the body of constitutional control is of great importance in the mechanismof legitimization of the government because it is intended to protect the fixed in the Constitution sovereign rights of citizens from illegal actions and decisions of public authorities, giving them additional legitimacy. The court is endowed with such authority because itperforms the role of the guardian of the Constitution, and is by its nature the social contract which, on the one hand, defines the basic rights and freedomsof a person and on the other – restricts the powers of the state. To implement the democratic legitimization the Constitutional Court of Ukraine must possess certain powers, which are now fixed in the Constitutions of the developed European countries.
Formation of the Ukrainian Constitutional Court as a Basis to Ensure its Legitimate Functioning.
Keywords: Конституційний суд України; формування суду; легітимність суддів; незалежність судової влади; Constitutional Court of Ukraine; the formation of the court; the legitimacy of judges; independence of the judiciary